Assessment of rotatory and reciprocating movements in root canal filling material removal - Maliza, Amanda Garcia Alves (2017)
The aim of this study was to evaluate the effects of preparation, filling removal material, reinstrumentation and reobturation of root canals with different Ni-Ti alloys in endodontic retreatment. Firstly, the selection and pairing of mesial root canals of mandibular molars (n = 45) were performed by computerized micro-tomography (micro-CT). After pairing, the specimens were divided into three groups (n = 15), instrumented with the Mtwo® (up to file 25.06), ProDesign Logic (25.06) and ProDesign R (25.06) systems. After this, the specimens were scanned again for root canal deviation analysis at 2, 4, 6, 8 and 10 mm from the apex and the volume increase of these root canals was evaluated through CTan Then, the root canals were filled with Endofill® with 0.1% rhodamine B and scanned in micro-CT once again. For the retreatment of the specimens, 3 groups were established according to the system used (Reciproc®, Hyflex® and ProDesign Duo Hybrid®). During the retreatment, the specimens were scanned in micro-CT in two more phases, after removal of filling material and after reinstrumentation of the root canals. All the images obtained previous and post-retreatment were compared to evaluate the capacity of removal filling material of each system through the volume of material remaining at 3mm in the apical third. Possible deviation of the root canal was assessed at 2, 4, 6, 8 and 10 mm from the apex. In addition, the times of preparation, removal filling material and reinstrumentation of these files were also evaluated. After the removal filling material and reinstrumentation of the root canals, they were refilled with AH Plus with 0.1% fluorescein. The specimens were sectioned crosswise into 2 mm slices to be analyzed by a confocal laser scanning microscope (CLSM) at 1, 3 and 5 mm from the apex, where the volume of material was evaluated through LAS X 3D and 2D software. The time of preparation, removal filling material and reinstrumentation of the root canals between the different systems was measured by a digital timer. The evaluation of canal volumetric increase and preparation time between Mtwo and ProDesign Logic systems were conducted using Student t-test analysis. Non-parametric Wilcoxon test was used to the intragroup comparison at the 2, 4, 6, 8 and 10 mm levels and non-parametric Mann-Whitney test was used to the comparison between groups in the root canal transportation in all sections of the root canal. The intra-group comparison regarding the presence or absence of root canal deviation after removal of root canal filling material and re-instrumentation was submitted to the parametric T-paired statistical test, since it had a normal distribution. The working time with the different alloys used to removal filling material an reinstrumentation was analyzed through parametric ANOVA e Tukey statistical test. The analysis of the remaining material present in the root canals was performed with nonparametric Kruskal-Wallis and Dunn tests. For the intra-group comparison between the different slices (1, 3 and 5 mm), the data were submitted to nonparametric Friedman and Dunn tests. The level of significance was established at 5% in all analysis. After the initial preparation of the root canals, the ProDesign Logic system proved to be faster than Mtwo system, with statistical difference between them (P <0.05). There was no statistical difference in root canal deviation after initial preparation and after retreatment (P> 0.05). In addition, the groups did not present a significant statistical difference to the volume increase of the root canals after the initial preparation or to the volume of filling material remaining after the retreatment (P> 0.05). The Reciproc system proved to be the fastest system for the removal filling material and reinstrumentation of the root canals (P <0.05). The present study demonstrated that the Prodesign Logic and Mtwo systems presented similar capacity of preparation of mesial root canals. The Reciproc, Hyflex and ProDesign Duo Hybrid systems are similar in the removal of filling material, preserving the original root canal shape in endodontic retreatment. However, Reciproc was the fastest compared to the other groups.